# Class 11 RD Sharma Solutions – Chapter 10 Sine and Cosine Formulae and Their Applications – Exercise 10.1 | Set 1

### Question 1: If in △ABC, ∠A=45°, ∠B=60°, and ∠C=75°, find the ratio of its sides.

**Solution:**

According to the sine rule

Attention reader! All those who say programming isn't for kids, just haven't met the right mentors yet. Join the

Demo Class for First Step to Coding Course,specificallydesigned for students of class 8 to 12.The students will get to learn more about the world of programming in these

free classeswhich will definitely help them in making a wise career choice in the future.Hence, we get

Using the formula,

sin (A+B) = sin A cos B + cos A sin Bsin (45°+30°) = sin(45°) cos(30°) + cos(45°) sin(30°)

sin 75° =

sin 75° =

Multiplying the denominator by 2√2, we get

Hence, we get

a : b : c = 2 : √6 : (√3+1)

### Question 2: If in △ABC, ∠C=105°, ∠B=45°, and a=2, then find b.

**Solution:**

In the given condition, ∠C=105° and ∠B=45°

And as we know that,

A+B+C = π(Sum of all angles in triangle is supplementary)A = π-(B+C)

A = 180°-(45°+105°)

A = 30°

Now, according the sine rule

After rationalizing the denominator, we get

### Question 3: In △ABC, if a=18, b=24, and c=30 and ∠C=90°, find sin A, sin B, and sin C.

**Solution:**

In the given condition, a=18, b=24 and c=30 and ∠C=90°

Now, according the sine rule

Also,

### Question 4: In △ABC, prove the following:

**Solution:**

According to the sine rule

Considering the LHS of the equation, we have

By using trigonometric formula,

sin A – sin B= 2 sincos

sin A + sin B= 2 sincosAs, LHS = RHS

Hence, proved !!

### Question 5: In △ABC, prove the following:

### (a-b)= c

**Solution:**

According to the sine rule

Considering LHS, we have

By using trigonometric formula,

sin A – sin B = 2 sincos= λ

A+B+C = π (Sum of all angles in triangle is supplementary)= 2λ sincoscos

= 2λ sincoscos

= λ sin(2cossin)

By using trigonometric formula,

2 sin a cos a = sin 2a= λ sin(sin)

= λ sinsin(A+B)

= λ sinsin(π-C)

(A+B+C = π)= λ sinsin(C)

= (λ sin C) sin

= c sin

As, LHS = RHS

Hence Proved!

### Question 6: In △ABC, prove the following:

**Solution:**

According to the sine rule

Considering LHS, we have

By using trigonometric identities,

sin A – sin B = 2 sincossin 2a = 2 sin a cos a

……………………….(1)Now considering RHS, we have

Cross multiplying we get,

By using trigonometric identities,

sin a cos b + cos a sin b = sin (a+b)

sin a cos b – cos a sin b = sin (a-b)

……………………….(2)As, LHS = RHS

Hence Proved!

### Question 7: In △ABC, prove the following:

**Solution:**

According to the sine rule

Considering LHS, we have

By using trigonometric identities,

sin A + sin B = 2 sincos

sin 2a = 2 sin a cos a

………………………….(1)Now considering RHS, we have

Cross multiplying we get,

By using trigonometric identities,

cos a cos b + sin a sin b = cos (a-b)

cos a cos b – sin a sin b = cos (a+b)

……………………….(2)As, LHS = RHS

Hence, Proved!

### Question 8: In △ABC, prove the following:

**Solution:**

According to the sine rule

Considering LHS, we have

By using trigonometric identities,

sin A + sin B = 2 sincos

sin 2a = 2 sin a cos aAs, LHS = RHS

Hence, Proved!

### Question 9: In △ABC, prove the following:

**Solution:**

According to the sine rule

Considering RHS, we have

By using trigonometric identities,

sin A – sin B = 2 sincosBy using trigonometric identities,

2 sin a cos a = sin 2aAs, LHS = RHS

Hence, Proved!

### Question 10: In △ABC, prove the following:

**Solution:**

According to the sine rule

Considering LHS, we have

By using trigonometric identities,

sin^{2}a – sin^{2}b = sin(a+b) sin (a-b)As, LHS = RHS

Hence, Proved!

### Question 11: In △ABC, prove the following:

### b sin B – c sin C = a sin (B-C)

**Solution:**

According to the sine rule

And, cosine rule,

Considering RHS, we have

RHS = a sin (B-C)

By using trigonometric identities,

sin(a-b) = sin a cos b – cos a sin b= a (sin B cos C – cos B sin C)

= a ((bλ)–(cλ))

= λ

= 2λ

= λb

^{2}-λc^{2}= b(λb) – c(λc)

= b(sin B) – c(cos C)

As, LHS = RHS

Hence, Proved!

### Question 12: In △ABC, prove the following:

### a^{2} sin (B-C) = (b^{2}-c^{2}) sin A

**Solution:**

According to the sine rule

Considering RHS, we have

RHS = (b

^{2}-c^{2}) sin A= λ

^{2}sin A(sin^{2}B – sin^{2}C)By using trigonometric identities,

sin^{2}a – sin^{2}b = sin(a+b) sin (a-b)= λ

^{2}sin A(sin(B+C) sin (B-C))= λ

^{2}sin A(sin(\pi-A) sin (B-C))= λ

^{2}sin A(sin(A) sin (B-C))= λ

^{2}sin^{2}A sin (B-C)= (λ sin A)

^{2}sin (B-C)= a

^{2}sin (B-C)As, LHS = RHS

Hence, Proved!

### Question 13: In △ABC, prove the following:

**Solution:**

Considering LHS, we have

LHS =

Rationalizing the denominator, we get

According to the sine rule

As, LHS = RHS

Hence, Proved!

### Question 14: In △ABC, prove the following:

### a (sin B – sin C) + b(sin C – sin A) + c(sin A – sin B) = 0

**Solution:**

According to the sine rule

Considering LHS, we have

LHS = a (sin B – sin C) + b(sin C – sin A) + c(sin A – sin B)

= λ sin A (sin B – sin C) + λ sin B (sin C – sin A) + λ sin C (sin A – sin B)

= λ sin A sin B – λ sin A sin C + λ sin B sin C – λ sin B sin A) + λ sin C sin A – λ sin C sin B

= 0

As, LHS = RHS

Hence, Proved!

### Question 15: In △ABC, prove the following:

**Solution:**

According to the sine rule

Considering LHS, we have

LHS =

=

= λ

^{2}sin A sin (B-C) + λ^{2}sin B sin (C-A) + λ^{2}sin C sin (A-B)By using trigonometric identities,

sin(a-b) = sin a cos b – cos a sin b= λ

^{2}(sin A [sin B cos C – cos B sin C] + sin B [sin C cos A – cos C sin A] + sin C [sin A cos B – cos A sin B])= λ

^{2}(sin A sin B cos C – sin A cos B sin C + sin B sin C cos A – sin B cos C sin A + sin C sin A cos B – sin C cos A sin B)= λ

^{2}(0)= 0

As, LHS = RHS

Hence, Proved!